2012
DOI: 10.4028/www.scientific.net/amm.239-240.932
|View full text |Cite
|
Sign up to set email alerts
|

Template Based Table Document Recognition

Abstract: In this paper we proposed an effective but simple table recognition algorithm in the OCR field. First a binary image template is built for the tables to be recognized, which consists of all the lines describing the table cells we are interested in. Then the images to be analyzed are thresholded and deskewed. Vertical and horizontal lines are extracted from the preprocessed image to form a table “scene”. Finally the binary image template is aligned to the table “scene” by minimizing their Hausdorff distance. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“… Rho et al (2020) identified the engineering drawings and extracted the row text in the document to automatically generate the building’s 3D model. Jia (2012) used template matching to identify the tables in the drawing to simplify the identification steps.…”
Section: Introductionmentioning
confidence: 99%
“… Rho et al (2020) identified the engineering drawings and extracted the row text in the document to automatically generate the building’s 3D model. Jia (2012) used template matching to identify the tables in the drawing to simplify the identification steps.…”
Section: Introductionmentioning
confidence: 99%